2020
DOI: 10.3346/jkms.2020.35.e7
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Decreasing Rate of HIV and HBV Co-infection in a Nationwide Korean HIV/AIDS Cohort

Abstract: From December 2006 to December 2016, 1093 human immunodeficiency virus (HIV) individuals < 70 years enrolled in Korea human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) cohort were analyzed to investigate the prevalence of HIV/HBV co-infection rate and hepatitis B virus surface antibody (HBsAb) positive rate based on birth year. The HBV co-infection prevalence rate was the highest (8.8%) in patients born between 1960 and 1964 and the lowest (0%) among those born between 1995 and 1999. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Similarly, a study of two moderate COVID-19 patients revealed that viral loads peaked at 3 to 5 days from first symptom onset and slowly decreased until the second week. Additionally, virus was detected in their lower respiratory systems before lower respiratory symptoms occurred [88]. More recent studies showed similar results.…”
Section: Differencse In Viral Load Between Mild and Severe Covid-19 Patientssupporting
confidence: 57%
“…Similarly, a study of two moderate COVID-19 patients revealed that viral loads peaked at 3 to 5 days from first symptom onset and slowly decreased until the second week. Additionally, virus was detected in their lower respiratory systems before lower respiratory symptoms occurred [88]. More recent studies showed similar results.…”
Section: Differencse In Viral Load Between Mild and Severe Covid-19 Patientssupporting
confidence: 57%
“…However, unlike findings from previous studies, our findings suggest that there was no significant increase in liver cancer caused by hepatitis B or C infection and lung cancer caused by smoking or pulmonary diseases in people with HIV in Korea. The prevalence of hepatitis B infection in a Korean HIV/AIDS cohort, including approximately 10% of people infected with HIV in Korea, was 5.2%, which was similar to that of the general population of men in Korea (4%-5%) . The prevalence of current smoking was comparable between individuals infected with HIV (42.8%) and Korean men (49.8%) .…”
Section: Discussionmentioning
confidence: 70%
“…Incident Cancer Cases and Incidence Rate of Cancer in Patients With HIV Infection 20 to 79 Years of Age in Korea, 2006-2018Cancer Incidence Among Adults With HIV in a Population-Based Cohort in Korea smoking or pulmonary diseases in people with HIV in Korea. The prevalence of hepatitis B infection in a Korean HIV/AIDS cohort, including approximately 10% of people infected with HIV in Korea,18 …”
mentioning
confidence: 99%
“…Reductions were also observed in South Korea and Taiwan; the prevalence of HBV in South Korea decreased from 8% to 3.7% after neonatal vaccination was introduced [13]. It also reduced in people living with HIV, from 8.8% for those born between 1960 and 1964 to 0% for those born between 1995 and 1999 [14]. In Taiwan, the rate of HIV‐HBV co‐infection in people living with HIV decreased from 18.1% in those born before the vaccination programme was introduced in July 1986 to 3.4% in those born after [15].…”
Section: Routes Of Transmissionmentioning
confidence: 99%